Evidence that a non-O1 Vibrio cholerae produces enterotoxin that is similar but not identical to cholera enterotoxin. - Yamamoto, K (1983)
Cholera-like enterotoxin produced by a non-O1 strain of Vibrio cholerae, S7 (S7 enterotoxin), isolated from human diarrheal stool, was purified, and its physicochemical, biological, and immunological properties were compared with those of cholera enterotoxin from V. cholerae O1 569B (CT) and an enterotoxin produced by another non-O1 V. cholerae (E8498 enterotoxin) reported previously (Yamamoto et al., Infect. Immun. 39:1128-1135, 1983). The purified S7 enterotoxin had physicochemical properties different from those of CT and E8498 enterotoxin. S7 enterotoxin had greater relative mobility in conventional polyacrylamide gel disc electrophoresis and a lower isoelectric point, and its B subunit was smaller than those of CT and E8498 enterotoxin. The results of sodium dodecyl sulfate-polyacrylamide slab gel electrophoresis suggested that the size of the aggregate of the B subunits of S7 enterotoxin is larger than that of CT and E8498 enterotoxin. The biological and immunological properties of S7 enterotoxin were indistinguishable from those of CT and E8498 enterotoxin. These results indicate that non-O1 vibrios may produce more than one kind of cholera-like enterotoxin: one which is identical to CT (E8498 enterotoxin type) and another which is not identical to CT (S7 enterotoxin type).